Pemanfaatan Model Pembelajaran Make A Match Dalam Pembelajaran Matematika: Studi Kasus Di Salah Satu Sekolah Dasar Islam - Awaliah, Nurlita; Fitri Yessi Jami; Fadilah Prabowo (STAI AL-AMIN, 2024)
In the learning process at school between educators and students there must be social interaction. As an educator, you should realize what should be done to be able to create a conducive learning environment for students in order to achieve the expected goals. Therefore, the selection of an interesting and fun learning model is needed. One of the learning models that can be applied to mathematics subjects in elementary schools is the make a match learning model. This study aims to determine the utilization of the make a match learning model as well as the teacher's handling in overcoming students who are left behind in mathematics learning through the make a match model. This research uses descriptive qualitative research. The data collection techniques used by researchers are observation, interviews, and documentation. The results of the study found that the utilization of the make a match learning model in one of the elementary schools in Karawang was planned in accordance with the Learning Implementation Plan (RPP) prepared by the teacher, with the implementation and learning process according to the stages, namely the initial activities, core activities, and closing activities. The teacher's handling in overcoming students who are lagging behind in learning are: 1) providing motivation to students, 2) conducting learning activities outside the classroom in order to facilitate the movement of students so that learning is easier.